An Unusual Case (Metastatic-Like Lesion) of Septic Cerebral Embolus Caused by Corynebacterium mucifaciens in a Diabetic Patient. (June 2020) - Senaobar Tahaei, Seyed Arad; Mencser, Zoltan; Reisz, Zita; Barzo, Pal
Septic cerebral emboli can be a challenging diagnosis to give, especially if atypical bacterial infections are the cause of it. Correct diagnosis of this condition can change the management route of the patient and result in a nonsurgical treatment. To our best knowledge, this is the first case of septic cerebral embolus caused by Corynebacterium mucifaciens reported. In this study, a 65-year-old diabetic patient who have developed ketoacidosis and went into coma was investigated for a case of septic cerebral embolization. The patient developed a sudden right-sided hemiparesis, and the radiological findings showed a tumor-like lesion on the left hemisphere at the level of the internal capsule. At first glance, presence of a metastatic tumor could not be excluded; therefore, further laboratory tests and examinations were done to rule out metastatic lesions. The blood culture of the patient revealed a case of bacteremia caused by Corynebacterium mucifaciens and then a septic cerebral embolus was suspected, but due to the rarity of this pathogen causing such complications as well as the similarity of the lesion to a metastatic brain tumor, a biopsy was performed and the histopathological findings confirmed the diagnosis of a septic cerebral embolus. Corynebacterium mucifaciens should be considered a human pathogen in immunocompromised patients and it can cause cerebral septic embolization. Metastatic brain tumors and tuberculomas should be excluded; if the uncertainty of a metastatic tumor remains, biopsy can be performed and histological findings can amplify the diagnosis of septic cerebral embolus.